2012
DOI: 10.1039/c1dt11338k
|View full text |Cite
|
Sign up to set email alerts
|

Nickel complexes incorporating an amido phosphine chelate with a pendant amine arm: Synthesis, structure, and catalytic Kumada coupling

Abstract: A series of organonickel(II) complexes incorporating an amido phosphine ligand tethered with an amino pendant have been prepared and characterized. Deprotonation of N-(dimethylaminoethyl)-2-diphenylphosphinoaniline (H[PNN]) with one equivalent of n-BuLi in ethereal or hydrocarbon solutions at -35 °C generates cleanly dimeric {Li[PNN]}(2) as yellow crystals. The reaction of NiCl(2)(DME) with {Li[PNN]}(2) in THF at -35 °C affords green crystalline [PNN]NiCl. Treating [PNN]NiCl with NaX in acetone solutions gives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 59 publications
0
10
2
Order By: Relevance
“…The Ni–C distances of the ethyl ligands bound to the nickel atom of 5 [1.986(3) Å] and 7 [1.991(2) Å] are slightly longer than the Ni–C methyl bonds in 3 and 4 . In the ethyl complexes, the distance Ni–C100 to the ethyl ligand of 5 [1.986(3) Å] and 7 [1.991(2) Å] are also slightly elongated in comparison to the bond length observed in [(PNN)NiEt] {1.960(3) Å} . The plane through the fluoroarene carbon atoms is almost perpendicular with respect to the Ni(NHC) 2 plane (plane through the nickel atom and the NHC carbene carbon atoms).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The Ni–C distances of the ethyl ligands bound to the nickel atom of 5 [1.986(3) Å] and 7 [1.991(2) Å] are slightly longer than the Ni–C methyl bonds in 3 and 4 . In the ethyl complexes, the distance Ni–C100 to the ethyl ligand of 5 [1.986(3) Å] and 7 [1.991(2) Å] are also slightly elongated in comparison to the bond length observed in [(PNN)NiEt] {1.960(3) Å} . The plane through the fluoroarene carbon atoms is almost perpendicular with respect to the Ni(NHC) 2 plane (plane through the nickel atom and the NHC carbene carbon atoms).…”
Section: Resultsmentioning
confidence: 96%
“…Selected bond lengths of 3 , 4 , 5 and 7 are given in Table and are compared to the known structure of 2 and [(PNN)NiEt] {PNN = N ‐(dimethylaminoethyl)‐2‐diphenylphosphinoanilin}. [11b], …”
Section: Resultsmentioning
confidence: 99%
“…Similarly, the nickel methyl complex based on an aliphatic phosphinite pincer ligand displayed a low reactivity and required harsh reaction conditions . We and others have found that complexes based on unsymmetrical pincer ligand scaffolds display unique chemical reactivities in comparison to the symmetrical scaffolds. ,,, We recently reported the first example of an unsymmetric aromatic PCN pincer nickel methyl complex and inter alia studied its reactivity toward CO 2 . However, this complex also showed low reactivity toward CO 2 and only 75% conversion was achieved at 150 °C and decomposition was observed during the carboxylation reaction.…”
Section: Introductionmentioning
confidence: 99%
“…The next biggest difference occurs in the Ni1‐Cl1 distance: the triclinic form measures 2.181 Å, slightly smaller than the average in the monoclinic form 2.185 Å. The Ni1‐Cl1 distances are at the longer end while the Ni1–P1 distances are at the shorter end of the ranges found in other (PNN)NiCl [ 26,28,29 ] or (PNP)NiCl [ 32,33,41 ] complexes. In 1‐Me , the five‐membered NC 2 PNi chelate ring adopts an envelope conformation (fold angles = 16.3° for P 1, 11.0° and 20.1° for rings involving Ni1 and N1a, respectively, in the monoclinic form) and the six‐membered NC 2 N 2 Ni chelate ring adopts a half‐boat conformation to give an overall structure that distinguishes the phenyl rings of the PPh 2 group (Figure 2, right), with a pseudoaxial ring (type A) being closer to the toluidinyl ring than the pseudoequatorial ring (type B).…”
Section: Resultsmentioning
confidence: 90%
“…We sought to extend these studies to pincer complexes with organophosphine donors. Despite numerous (PNN)Ni pincer complexes being known as catalysts for a variety of reactions, [ 23–29 ] it was fairly surprising that there were no reports of their use as catalysts for HDH reactions. Several years ago, our group introduced a PNN pincer type ligand, ( N ‐2‐diphenylphosphinophenyl)( N ‐2‐pyrazolyl‐ p ‐tolyl)amine, H(PNN–Me), and showed that the hemilabile pyrazolyl arm conferred enhanced reactivity and structural adaptability to stabilize various rhodium(I/III) complexes.…”
Section: Introductionmentioning
confidence: 99%